Karakteristik Ibu dan Faktor Risiko Kejadian Kematian Bayi di Kabupaten Banjarnegara - Kusumawardani, Annisa; Handayani, Sri (Jurnal Promosi Kesehatan Indonesia, 2018)
Background: The number of infant mortality in Banjarnegara district became the highest compare with other districts in Central Java in 2012. In the last 5 years, infant mortality rate in this district has not been significantly declined. This study aims to analyze mother’s characteristics and some risk factors associated to infant mortality in Banjarnegara.Method: This study is survey with case control approach, sample consists of 47 mothers of having infant death before aged 24 days and 47 mothers as a control. Sample has been selected using purposive sampling. Primary data were collected by using face to face interview with questionnaire and secondary data collected based on mother health’s book record in health center. Data was analyzed by frequency distribution and Chi- Square test.Results: The Result showed that the risk factors which associated to infant death were baby with delivery complication, mother with history of anemia, baby with underweight birth, baby with asphyxia, congenital illness and premature birth. Whilst mother’s age, mother’s knowledge mother’s education, parity, mother’s weight, upper arm circumference of mother, mother with chronic diseases history, and bleeding experience during pregnant, hypertension, birth attendant, and mother’s literacy had no significant association to infant death. This study recommends that health provider (especially village midwife) of health center have to prevent the risk factors of infant death by visiting mother with some risks intensively and routinely including Fe provision. The mother with some risks has to visit health center or health service in their village to check their infant.Keywords: infant death, mother risk characteristics, risk factors